2002
DOI: 10.1128/jvi.76.12.6268-6286.2002
|View full text |Cite
|
Sign up to set email alerts
|

1-β- d -Arabinofuranosylcytosine Inhibits Borna Disease Virus Replication and Spread

Abstract: Borna disease virus (BDV) is a nonsegmented, negative-strand RNA virus that causes neurological diseases in a variety of warm-blooded animal species. There is general consensus that BDV can also infect humans, being a possible zoonosis. Although the clinical consequences of human BDV infection are still controversial, experimental BDV infection is a well-described model for human neuropsychiatric diseases. To date, there is no effective treatment against BDV. In this paper, we demonstrate that the nucleoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Since in vivo, BDV replicates and persists predominantly in neurons of the limbic system, we used primary cultures of rat hippocampal neurons. After in vitro infection with BDV-CRV, BDV efficiently replicated in cultured neurons, confirming previous observations (1). To selectively study the process of virus dissemination and to separate this process from the primary infection with BDV-CRV, we performed the initial infection with BDV-CRV at a low MOI (0.025 FFU/cell).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Since in vivo, BDV replicates and persists predominantly in neurons of the limbic system, we used primary cultures of rat hippocampal neurons. After in vitro infection with BDV-CRV, BDV efficiently replicated in cultured neurons, confirming previous observations (1). To selectively study the process of virus dissemination and to separate this process from the primary infection with BDV-CRV, we performed the initial infection with BDV-CRV at a low MOI (0.025 FFU/cell).…”
Section: Discussionmentioning
confidence: 76%
“…In vivo, BDV replicates and persists predominantly in neurons of the limbic system. Recently, it was shown in vitro that rat hippocampal neurons are highly susceptible to infection with cell-free BDV (1). In order to assess whether BDV-GP is required for neuronal dissemination of BDV, we used primary cultures of rat hippocampal neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was surprising to find that it could inhibit BDV, a negative-stranded RNA virus that synthesizes only RNA. In addition, the effect against BDV could not be attributed to any known effect of Ara-C on the host cell (1). Therefore, we sought to elucidate the mechanism of action of Ara-C on BDV.…”
mentioning
confidence: 99%
“…Previously, we showed that inhibition of BDV replication by Ara-C was associated with a nuclear retention of BDV antigens in infected cells (1). We took advantage of this characteristic to rapidly screen 2Ј-FdC and gemcitabine for their potential to inhibit BDV replication in Vero cells that were persistently infected with BDV (i.e., Vero-BV).…”
mentioning
confidence: 99%